Desertification Monitoring Using Remote Sensing and GIS Techniques (Iraqi Journal of Civil Engineering, 2017)
Proliferated in recent years the desertification phenomenon, and the desert areas started expanding at the expense of green areas, which affected the environment. This research focused on studying the desertification and its changes regarding to the time, through using different multi band satellite images for the area of interest in different times and studying the changes appear to the land cover and calculating the areas of each parameter to make the comparison for each environmental parameter (soil, agriculture, and water).